2020
DOI: 10.35790/eg.8.2.2020.30541
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Metode Third Molar Maturity Index pada Kelompok Usia Remaja

Abstract: Up to now, there are still residents of Indonesia who do not have legal documents supporting age information. Hence, proving the age of a person concerning some reasons becomes difficult. Third molar development could be used as an indicator to estimate the age in adolescents if legal documents are not available. This study was aimed to prove the difference in the development of third molars between individuals aged above and below 19 years using the third molar maturity index (I3M) method. Third molar develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, for I3M methods by Cameriere et al specific model has not yet been analyzed as the I3M method is more commonly used to assess legal age by using a specific cut-off value of <0.08, evaluated for applicability and reliability in different populations (Gomez Jimenez et al, 2019;Rozylo-Kalinowska et al, 2018). Prabowo et al showed significant differences between the I3M index between individuals above and below 19 years old, and there were no differences between females and males (Prabowo et al, 2020). As a binomial factor can determine the indication of adult age (e.g., above or below a certain age), an application of a classification model, such as SVM, can be applied.…”
Section: Resultsmentioning
confidence: 99%
“…However, for I3M methods by Cameriere et al specific model has not yet been analyzed as the I3M method is more commonly used to assess legal age by using a specific cut-off value of <0.08, evaluated for applicability and reliability in different populations (Gomez Jimenez et al, 2019;Rozylo-Kalinowska et al, 2018). Prabowo et al showed significant differences between the I3M index between individuals above and below 19 years old, and there were no differences between females and males (Prabowo et al, 2020). As a binomial factor can determine the indication of adult age (e.g., above or below a certain age), an application of a classification model, such as SVM, can be applied.…”
Section: Resultsmentioning
confidence: 99%